2018
DOI: 10.3233/jad-170862
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Sideritis scardica and Cichorium spinosum against Amyloidogenic Pathway and Tau Misprocessing in Alzheimer’s Disease Neuronal Cell Culture Models

Abstract: These findings suggest that C. spinosum and S. scardica could have a notable potential in the prevention and/or treatment of AD, and merit further investigations at the in vivo level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 93 publications
3
14
0
Order By: Relevance
“…4 c). This is in accordance with previous findings in the specific plants [10,[28][29][30][32][33][34][35][36][37][38][39][40].…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…4 c). This is in accordance with previous findings in the specific plants [10,[28][29][30][32][33][34][35][36][37][38][39][40].…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…Tau hyperphosphorylation is believed to be crucial in AD pathogenesis by promoting the formation of NFTs and ultimately neural loss. We have previously demonstrated that tau is hyperphosphorylated at Thr231 and Ser199/Ser202 in PC12-htau cells compared to PC12 cells (Chalatsa et al, 2018). We therefore proceeded to assess the effects of trans -crocin 4 and trans -crocetin on this molecular mechanism using differentiated PC12-htau cells expressing hyperphosphorylated human tau.…”
Section: Resultsmentioning
confidence: 93%
“…A rapid and accurate method was developed, aiming to detect the major active compounds in the H. perforatum extract, as described elsewhere 30 . For the LC-HRMS, an Orbitrap high resolution mass analyzer was used in negative ionization mode.…”
Section: Resultsmentioning
confidence: 99%